The methodology for defect quantification in concrete using IR thermography - Milovanović, Bojan; Banjad Pečur, Ivana; Štirmer, Nina (Journal of Civil Engineering and Management, 2017)
This paper presents a procedure for detecting and quantifying defects in reinforced concrete structures by us-ing the method of active infrared thermography (IRT). For quantitative analysis, a methodology of thermal stimulation of concrete specimens and post-processing of the gathered data was developed. Presented methodology uses principles of step heating (SH) thermography, pulsed phase (PPT) thermography, principal component thermography (PCT) and correlation operators technique. A short descriptions of the post-processing methods used in the research is also provided in the paper. All three post-processing methods i.e. PPT, PCT and correlation operators technique have shown the pos-sibility to enhance the defect detection in concrete structures in comparison to raw thermograms. According to the data accessible to the authors, in presented research, correlation operators and PCT post-processing techniques are being suc-cessfully used for the first time for defect detection within concrete structures. The results of the research clearly show the possibility of using active IRT for the detection and assessment of defect depth (quantification) in reinforced concrete structures with the measurement error within 10%.